What do we know about the genetic background of primary ciliary dyskinesia (PCD) and the reproductive approach? - Vujisić-Živković, Sanja (Array, 2019)
Introduction: Primary ciliary dyskinesia (PCD; MIM 244400) is a heterogeneous autosomal recessive genetic disorder associated with infertility due to impaired sperm motility in men. We describe two such cases and give a literature review on the genetic background and reproductive outcome. Materials and methods: Two primary infertile couples were referred to our clinic. Native semen, analyzed according to the WHO manual (2010), showed that male partners have completely immotile sperm with a negative pentoxifylline test. Sample vitality was compared according to different semen preparation methods (gradient density and washing method only). Genetic testing was done by Whole Exome next-generation Sequencing (WES) analysis. For the IVF/ICSI procedure, semen was prepared using the gradient density method, and prior to the ICSI procedure itself, a hypo-osmotic swelling test (HOST) was done. Results: Semen analysis showed oligoasthenozoospermia in Patient 1 and oligoasthenoteratozoospermia in Patient 2. Blood draw for hormones and karyotype showed no irregularities in either case. Patient 1 was previously diagnosed with PCD, while Patient 2 was not. Parallel vitality testing did not show any differences between the two semen preparation methods in either of the two cases. Genetic testing in Patient 2 showed a pathogenic apparently homozygous CCDC40:c.2440C>T variant in exon 14 of the CCDC40 gene (MIM 613799). Fertilization rate after HOST/ICSI in both patients was 100%, and the final outcome for both patients was the birth of a healthy child. Conclusion: Although PCD has diverse etiology, assisted reproduction techniques such as HOST give these couples a good chance for parenthood. Advances in testing and strict adherence to advised procedures are to be credited for such outcome improvement. Additionally, our recommendation for PCD patients and patients with immotile sperm is to do genetic testing and counselling prior to the IVF/ICSI procedure.